EDUKASI DAN EVALUASI TINGKAT PENGETAHUAN WARGA SEKITAR MASJID DI DAERAH PEKALONGAN BARAT MENGENAI PENGGUNAAN HANDSANITIZER GUNA PENCEGAHAN COVID-19 - Kharismatul Khasanah; Metha Anung Anindhita; Ekanita Desiani; Siska Rusmalina (PENA ABDIMAS : Jurnal Pengabdian Masyarakat, 2021)
Corona virus or severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a virus that attacks the respiratory system. The disease due to this infection is called COVID-19. Corona virus can cause respiratory system disorders, acute pneumonia, and death. Prevention of coronavirus can be started from ourself. One of the things that can we do is to know the current information about the Covid-19 pandemic on the WHO website and through public health authorities. WHO advises all of us to avoid novel Covid-19 virus infection by maintaining our health and protecting others.One of them is by doing hand washing using a handsanitizer. These handsanitizers are a new habit and need to be done consistently. In order to prevent the maximum transmission, we must use a handsanitizer appropriately. It is intended that the worship process at the mosque can continue and also to prevent the transmission of Covid-19. This method of community service is the manufacture and distribution of handsanitizer and education of the use of a good and correct handsanitizer to the residents around the mosque. The Community Service Activities Program carried out can provide benefits to the community in the knowledge of using Handsanitizer correctly in preventing the transmission of novelcorona virus (Covid-19). Keyword : Covid-19, Handsanitizer, prevention